2013
DOI: 10.1093/cercor/bht164
|View full text |Cite
|
Sign up to set email alerts
|

Neuroelectrical Decomposition of Spontaneous Brain Activity Measured with Functional Magnetic Resonance Imaging

Abstract: Spontaneous activity in the human brain occurs in complex spatiotemporal patterns that may reflect functionally specialized neural networks. Here, we propose a subspace analysis method to elucidate large-scale networks by the joint analysis of electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) data. The new approach is based on the notion that the neuroelectrical activity underlying the fMRI signal may have EEG spectral features that report on regional neuronal dynamics and interregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 60 publications
1
28
2
Order By: Relevance
“…The scale-free component is arrhythmic and not confined to any specific time scale (Yamamoto et al, 1991); its power spectrum follows a power-law distribution, shown as a descending line on the log-log plot (Miller et al, 2009;He, 2014). In contrast, the oscillatory component contains rhythms indicative of neural dynamics with characteristic time scales (Buzsáki and Draguhn, 2004); it typically exhibits one or multiple spectral peaks at specific frequencies. Based on their distinct temporal and spectral characteristics, we were able to separate the scale-free and oscillatory components in the power spectrum of the neurophysiological signal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale-free component is arrhythmic and not confined to any specific time scale (Yamamoto et al, 1991); its power spectrum follows a power-law distribution, shown as a descending line on the log-log plot (Miller et al, 2009;He, 2014). In contrast, the oscillatory component contains rhythms indicative of neural dynamics with characteristic time scales (Buzsáki and Draguhn, 2004); it typically exhibits one or multiple spectral peaks at specific frequencies. Based on their distinct temporal and spectral characteristics, we were able to separate the scale-free and oscillatory components in the power spectrum of the neurophysiological signal.…”
Section: Resultsmentioning
confidence: 99%
“…fMRI has been used increasingly to uncover large-scale neural networks with correlated spontaneous activity in the absence of any overt task (Biswal et al, 1995). These resting-state networks (RSNs) mostly appear modular (Van Dijk et al, 2010), arise from structural connections (Greicius et al, 2009), persist across behavioral states , and resemble task activa-tion patterns (Smith et al, 2009), thereby being recognized to report on the brain's intrinsic functional organization (Fox and Raichle, 2007;Power et al, 2011;Yeo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, beta rhythms are associated with activation of the primary somatosensory and motor cortices (Liu et al 2014;Ritter et al 2009). We found delta/theta frequency tuning in the pulvinar, as visualized in map D and F. This finding contrasts with the finding that the pulvinar can act as a posterior alpha generator (Liu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cortical maps of spectral EEG signatures during spontaneous fMRI signals were created and used to determine clusters of brain areas that represent prominent functional subdivisions (Liu et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…imultaneous acquisition of functional magnetic resonance imaging (fMRI) in combination with electroencephalography (EEG), electrocorticography (ECoG), local field potentials (LFP), and single or multi-unit activity (SUA/MUA) holds great potential to bridge brain activity across spatial and temporal scales [1]- [10]. Despite its scientific premise and clinical This potential, concurrent electrophysiological (EP) and MRI acquisition is challenging, since the MRI apparatus presents a hostile environment for recording bioelectric signals [3], [5], [8], [11].…”
Section: Introductionmentioning
confidence: 99%